Optimization of process parameters using response surface methodology for essential oil extraction from Canarium odontophyllum kernels by subcritical water treatment - Hamzah, Muhammad Hazwan; Zulkefli, Nurbalqis; Aili Hamzah, Adila Fazliyana; Shamsudin, Rosnah; Che Man, Hasfalina; Md Ali, Abd Halim; Mohd Ali, Maimunah; Maringgal, Bernard; Wondi, Mohd Hafizz (Springer, 2024)
The physicochemical properties of dabai kernel oil as well as the morphology of dabai samples are affected by the optimal extraction method and process configurations. Subcritical water treatment prior to dabai kernel oil extraction was optimized through the utilization of response surface methodology based on central composite design. The subcritical water treatment was carried out within the following temperature ranges of 100 to 150 °C, 10- to 20-min reaction times, and 10:1 to 20:1 solvent to solid ratios. Results showed that temperature of 100 °C, reaction time of 10 min, and solvent to solid ratio of 10:1 were optimal parameters for dabai kernel oil by subcritical water treatment prior to Soxhlet extraction. Dabai kernel oil yields via subcritical water treatment were 96.53% on average, compared to 42.85% for Soxhlet extraction sample. Gas chromatography mass spectrometry analysis found for subcritical water treatment samples revealed value-added compounds, including oxalic acid and 9-octadecenoic acid, which can be utilized for cleaning and pharmaceutical applications. Scanning electron microscope images provided evidence that rapid extraction was driven by the degradation and aggregation of dabai kernel powder structure. The Brunauer–Emmett–Teller analysis indicated that the dabai kernel of subcritical water treatment displayed a greater surface area (14.813 m2/g) than the raw (2.804 m2/g) or Soxhlet extraction (13.452 m2/g) dabai kernel. Subcritical water treatment could be considered a promising method in combination with Soxhlet extraction in order to improve the oil yield from dabai kernels.